Odpowiedzi

2010-03-21T21:10:20+01:00
Z. 11
a) x/3 + 1 = 5/6 + x/2 /*6
x/3 * 6 + 1 * 6 = 5/6 * 6 + x/2 * 6
2x + 6 = 5 + 3x
2x - 3x = 5 - 6
-x = -1 / :(-1)
x = 1

b) (2x-3) : 4 = 1/2 + x /*4
4 * (2x-3) :4 = 1/2 * 4 + x * 4
2x - 3 = 2+ 4x
2x - 4x= 2+3
-2x = 5 /:(-2)
x = -2,5

c) (x+2) : 9 + (x-1) :3 = 1 /*9
x + 2 + (x-1) *3 = 9
x + 2 + 3x -3 = 9
x+ 3x = 9-2+3
4x = 10 /:4
x= 2,5

d) (2x + 3) :5 = (2-x) :3 + x /*15
6x + 9 = 10 - 5x +15x
6x+5x-15x = 10-9
-4x = 1 /:(-4)
x= - 0,25

e)(3x-5) :2 - (5x -1):10 = 0 /*10
15x - 25 - 5x +1 = 0
15x - 5x = 0 +25 -1
10x = 24 /:10
x = 2,4

f) x/2 = 2/5(4-x) -4 /*10
5x = 4(4-x) -40
5x = 16-4x-40
5x+4x = 16-40
9x = -24 /:9
x= -2 2/3

g) (2x-1) :5 - (x-2):2 = 0,7x
4x -2-5x+10 = 7x
4x - 5x -7x = 2-10
-8x = -8 / : (-8)
x=1

h) 2x - (3x+5):4 = -1/4x -1 /*4
8x- (3x+5) = -x-4
8x-3x-5 = -x-4
8x - 3x+x = -4+5
6x = 1 /:6
x= 1/6

Z.8
a) 4x - 3 = 3x +5
4x - 3x = 5 +3
x = 8

b) 5x +2 = 7-3x
5x +3x = 7-2
8x = 5 /:8
x = 5/8

c) 3(x-1) = 0
3x -3 = 0
3x = 3 /:3
x = 1

d) -6(x+1) =24
-6x -6 = 24
-6x = 24 +6
-6x = 30 /:(-6)
x = -5

e) -7(x-2) = 3x -1
-7x+14=3x -1
-7x - 3x = -1-14
-10x = -15 /:(-10)
x = 1,5

f) 4(x-1) = 6(1+x)
4x-4 = 6 + 6x
4x - 6x= 6+4
-2x = 10 /:(-2)
x = -5
87 4 87